2007
DOI: 10.1007/s10858-006-9132-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of hydrogen bonds of DNA and RNA to hydration, as gauged by 1 J NH measurements in ethanol–water mixtures

Abstract: Hydrogen-bond lengths of nucleic acids are (1) longer in DNA than in RNA, and (2) sequence dependent. The physicochemical basis for these variations in hydrogen-bond lengths is unknown, however. Here, the notion that hydration plays a significant role in nucleic acid hydrogen-bond lengths is tested. Watson-Crick N1...N3 hydrogen-bond lengths of several DNA and RNA duplexes are gauged using imino 1J(NH) measurements, and ethanol is used as a cosolvent to lower water activity. We find that 1J(NH) values of DNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…The chemical shifts of these amide protons of thymine and uracil in the complexes of T‐C16/A‐C16 and U‐C16/T‐C16 were used to obtain values of K a of 534 and 671 M –1 from Benesi–Hildebrand plots, respectively (see Supporting Information). The 1 H NMR titration experiments reveal that the hydrogen bonding strength of the U‐A base pair of RNA is stronger than that of T‐A base pair of DNA as previously described,3, 8, 9 indirect representing the relatively stronger strength of hydrogen bonding interaction within PVBU/PVBT complex.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…The chemical shifts of these amide protons of thymine and uracil in the complexes of T‐C16/A‐C16 and U‐C16/T‐C16 were used to obtain values of K a of 534 and 671 M –1 from Benesi–Hildebrand plots, respectively (see Supporting Information). The 1 H NMR titration experiments reveal that the hydrogen bonding strength of the U‐A base pair of RNA is stronger than that of T‐A base pair of DNA as previously described,3, 8, 9 indirect representing the relatively stronger strength of hydrogen bonding interaction within PVBU/PVBT complex.…”
Section: Resultssupporting
confidence: 61%
“…Only a limited number of reports have appeared so far to compare the hydrogen bonding interactions between DNA (T‐A) and RNA (U‐A) base pairs 1–7. Recently, Wang and coworkers8, 9 compared 2h Δ 13 C2 DNA and 2h Δ 13 C2 RNA and indicated that the RNA (U‐A) hydrogen bond is about 3% stronger than the DNA (A‐T) hydrogen bond.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical shifts of these amide protons of thymine and uracil in the complexes of T-C16/A-C16 and U-C16/T-C16 were used to obtain values of K a of 534 and 671 M -1 from Benesi-Hildebrand plots, respectively (see Supporting Information). The 1 H NMR titration experiments reveal that the hydrogen bonding strength of the U-A base pair of RNA is stronger than that of T-A base pair of DNA as previously described, 3,8,9 indirect representing the relatively stronger strength of hydrogen bonding interaction within PVBU/ PVBT complex. Figure 3 displays DSC traces of PVBT/PVBA and PVBU/PVBA complexes, indicating that the glass transition temperatures (T g ) of pure PVBT and PVBU are about 188 and 141 C, respectively.…”
Section: Comparison Of Hydrogen Bonds Between the T-a And U-a Base Pairssupporting
confidence: 62%
“…In order to determine if either or both of these characteristics are present, we examined the impact of temperature on 1 J NH . The magnitude of 1 J NH has previously been used as an effective tool for detecting hydrogen bonds in biomolecules,47, 48 mainly because 1 J NH is not affected by changes in ϕ/ψ torsion angles. Analogous to the effect of temperature change on averaged NH chemical shifts, as described above, increase in sample temperature also influences average 1 J NH values due to an increase in the population in low‐lying unfolded states.…”
Section: Resultsmentioning
confidence: 99%